Subsidi Silang Praktik Pengabenan Berbasis Manajemen Upacara di Desa Penyaringan Kabupaten Jembrana - Subawa, I Made Pasek (Jayapangus Press, 2023)
Conducting cremation ceremony (ngaben) with conventional options as well as in the crematorium essentially requires costs in procuring various ceremonial supplies. Conventional cremation takes a lot of time, cost, and effort which is considered heavy, but it contains a lot of local wisdom values in each process. Meanwhile, crematoriums are considered effective, practical, and efficient in accordance with the needs of society in the midst of social problems and heterogeneous work that demands the various interests it has. However, the commodification system in the crematorium will degrade the local wisdom of the process of menyamabraya, nguopin, and learning about upakara ngaben that can naturally be formed in society. Through cross-subsidies with ceremonial management mechanisms, the two aspects are actually well bridged. The purpose of this study was to analyze the impact of cross-subsidies in the management of beneficiation ceremonies in Penyaringan village. This research uses qualitative methods with a phenomenological approach, to obtain data, it begins with determining the location, determining informants, collecting data, analyzing data, and is presented in a qualitative descriptive form. From the results of the study ceremonial management technically regulates the implementation of ceremonies that adopt modern management that regulates aspects of time and energy, while cross-subsidies have an impact on the provision of economic capital through the use of patus and peson-peson upakara. With this pattern, everyone who dies conducting cremation ceremony simply without having to be constrained in terms of his financing. Through ceremonial management, the values of local wisdom can still be maintained without having to put aside technological developments as a form of progress of the times.